Let’s Talk AI: Interdisciplinarity Is a Must (Lecture Notes in Computer Science; Computer Science; Computer Science (R0), 2026)
This unique open access volume represents an interdisciplinary dialog with top-class researchers and practitioners on the Artificial Intelligence revolution. The contributions derive from structured interviews with community leaders who examine recent developments in AI and offer predictions about its impact on science, technology, business, and society. The interviewees, leading thinkers and practitioners from fields such as Computer Science, Software Engineering, Philosophy, Psychology, and Law, gathered at the multidisciplinary event AISoLA, where they discussed developments in AI technologies, tools, and research, and these exchanges were shaped into this coherent survey. In the debates surrounding the rapid advancement of AI it’s clear that while there is much sharing of ideas, in fact true cooperation and alignment is rare, most fields still operate in silos. Given the pervasive nature of AI, it’s critical that we move forward carefully to ensure that our decisions and progress are well-considered. This book serves as a call to action, reminding us of our collective responsibility to shape the future. The authors offer points of agreement and contrast, the reader will better understand how we may still maintain control over technological progress in AI and its societal impact.